PESAN DAKWAH DALAM FILM HOROR RELIGI “MUNAFIK 2” (ANALISIS SEMIOTIKA ROLAND BARTHES) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This research discusses the Message of Proselytizing in the Religious Horror Film "Hypocritical 2 (Semiotic Analysis of Roland Barthes). This study aims to (1) find out what proselytizing messages are contained in the Religious Horror Film "Hypocritical 2" which airs on the big screen (2) know the meaning of the signs in the Religious Horror Film "Hypocritical 2" which airs on the big screen. This research uses qualitative methods. The data collection technique uses observation and documentation techniques, namely downloading the Religious Horror Film "Hypocritical 2" via the internet. Researchers classified some snippets of scenes from the Religious Horror Film "Hypocritical 2" and then sorted out the scenes containing proselytizing messages for deeper study. Data analysis using Roland Barthes' semiotic analysis method. The results of the study obtained after analyzing the Religious Horror Film "Hypocritical 2" (Semiotic Analysis of Roland Barthes) showed that (1) The proselytizing messages of the film shown Religious Horror Film "Hypocritical 2" containing the message of proselytizing categorized in the form of proselytizing, akidah, shari'ah (worship) and moral messages. (2) The meaning of the signs contained in the Religious Horror Film "Hypocritical 2" using Roland Barthes's semiotic theory of Connotative and Denotative signs.